Mapping the Intersection of Ecolinguistics and Critical Discourse Analysis: A Bibliometric Approach - Kamarullah Kamarullah; Lola Adres Yanti (SAWERIGADING, 2024)
Ecolinguistics explores the interplay between language and the ecological environment, encompassing humans, animals, and nature. Recent research trends have increasingly focused on critical discourse analysis (CDA), potentially overshadowing foundational ecolinguistic principles. This study conducted a bibliometric analysis of Scopus-indexed ecolinguistics publications from 2011 to 2022. The methodology involved collecting relevant publications, sorting and correcting metadata, and performing a bibliometric analysis using tools like VOSviewer and Mendeley Desktop. The analysis addressed publishing trends, citation patterns, author collaborations, keyword trends, abstract content, contributing nations, and key topics within ecolinguistics and CDA. Findings reveal (1) erratic growth in ecolinguistics publications, (2) fluctuating citation counts, (3) infrequent collaboration among authors, (4) a strong association of specific keywords, (5) significant connections in abstract content, (6) the United Kingdom and the United States as leading contributors, and (7) identification of 17 specific topics within ecolinguistics. The study highlights a lack of sustained interest in ecolinguistics, with a disproportionate focus on CDA, suggesting the need for a more balanced approach that incorporates comprehensive ecological issues. Enhanced data and perspectives from ecolinguistics should inform and expand discourse function theories.